Power supply system for smart contact lens - Haziq Raihan Mohd Aidit (Nanyang Technological University, 2022)
The development of a smart contact lens is a promising aspect in wearable devices in the future for various medical applications. A major challenge that affects the development of smart contact lens is finding a suitable power supply that abides by the safety regulations imposed for wearable devices worn on the eye. The objective of this project is to study and fabricate an aqueous battery that is flexible and biocompatible to the human eye. The material used for the battery electrode is Prussian Blue Analogues (PBAs). The battery is designed to operate safely in a tear-based solution, similarly to the surrounding environment of the human eye. Cyclic voltammetry (CV) and galvanostatic cycling with potential limitation (GCPL) curve tests are used to evaluate the performance of the battery.